Concentration Obstacles and High Mobility Behavior in a Senior Kindergarten Student: A Case Study - Jelina, Mariana (CV. Chandralia Bintang Pustaka, 2026)
AbstractThis study aims to provide an in-depth analysis of inattentive behavior and high mobility in a KindergartenB child during classroom learning activities. The study was conducted using a qualitative case study approachat TK Strada Budi Luhur from November 10 to December 2, 2025. Data were collected through naturalisticclassroom observations, in-depth interviews with teachers and family members, and supportingdocumentation. The findings indicate that the child exhibited a very short attention span and frequentwalking behavior, particularly during activities requiring sustained concentration and fine motor skills. Thewalking behavior functioned as a response to task difficulty, boredom, and sensory needs. Familyenvironmental factors, especially parental emotional conditions and limited home stimulation, alsoinfluenced the child’s self-regulation. Simple classroom strategies such as seating adjustments and structuredsensory breaks were effective in reducing high mobility behavior. This study contributes practical andtheoretical insights for early childhood educators in addressing attention difficulties through contextual andresponsive interventions.